Universal revolutionary pedagogical principles. The Ferrer Guardia´s Modern School - Nadal-Masegosa, Antonio (Akita International University, 2024)
The Modern School was an experience that, from Barcelona, sought to spread an emancipatory culture not only locally, but worldwide. A conscientious virtual ethnography with sources of high academic level, which include doctoral theses from recent years, allows us to know how the ideas of rationalist teaching that the creator of the school, Francisco Ferrer Guardia, promulgated, were penetrating Latin America, where there were several experiences, despite the diversity of countries and specific contexts. A culture in opposition to hegemony was possible, even though some of its postulates still seem distant today. Rationalist teaching, from this perspective, had and still has the aim of destroying atavisms, teaching truths, forming characters, preventing the formation of sectarian and unconscious masses, and making every man and woman a thinking and active being, over whom no false prestige or undue authority can be placed. Education and research with similar values are also possible today.
La Escuela Moderna fue una experiencia que, desde Barcelona, ​​buscó difundir una cultura emancipadora no sólo a nivel local, sino mundial. Una concienzuda etnografía virtual con fuentes de alto nivel académico, que incluyen tesis doctorales de años recientes, permite conocer cómo las ideas de la enseñanza racionalista que promulgó el creador de la escuela, Francisco Ferrer Guardia, fueron penetrando en América Latina, donde hubo varias experiencias, a pesar de la diversidad de países y contextos específicos. Era posible una cultura en oposición a la hegemonía, aunque algunos de sus postulados todavía hoy parezcan lejanos. La enseñanza racionalista, desde esta perspectiva, tuvo y tiene como finalidad destruir atavismos, enseñar verdades, formar caracteres, impedir la formación de masas sectarias e inconscientes, y hacer de cada hombre y mujer un ser pensante y activo, sobre el que no se puede colocar ningún falso prestigio ni autoridad indebida. También hoy son posibles una educación y una investigación con valores similares, más allá de los discursos reformistas, socialdemócratas e hipócritas.
Keywords: Educación - Historia; Anarquismo; América; Anarquism; Educational History; Historia de la Educación; Teoría de la Educación; Educational Theory; Ferrer Guardia; Escuela Moderna; Modern School; Revolución; Revolution